Remarkable books a celebration of the world's most beautiful and historic works - Collins, Michael 1960-; Black, Alexandra; Cussans, Thomas; Farndon, John; Parker, Philip 1965- (Dorling Kindersley Limited, 2017)
A beautifully illustrated guide to more than 75 of the world's most celebrated, rare, and seminal books and handwritten manuscripts ever produced, with discussions of their purpose, features, and creators. From ancient masterpieces such as The Art of War, written on the leaves of bamboo, to the stunningly illustrated Birds of America, to Chairman Mao's Little Red Book, [this book] delves into the stories behind the most incredible tomes ever produced, offering an insight into their wider social and cultural context, and is chronologically ordered to demonstrate the synergies between the growth in human knowledge and the bookmaking process